2022
DOI: 10.3389/fmed.2022.822964
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Changeover Time Between Surgeries Through Lean Thinking: An Action Research Project

Abstract: BackgroundMaximizing the utilization of the operating room suite by safely and efficiently changing over patients is an opportunity to deliver more value to patients and be more efficient in the operating suite. Lean Thinking is a concept that focuses on the waste inadvertently generated during organization and development of an activity, which should maximize customer value while minimizing waste. It has been widely applied to increase process efficiency and foster continuous improvement in healthcare and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…On the contrary, two non-significant increases in TOT after the intervention were reported [ 33 , 93 ]. TOT was measured in various settings, including pediatric facilities [ 69 ], ambulance services [ 125 ], pharmacies [ 33 ], and operating rooms [ 93 , 126 ]. Table 5 depicts the findings of TOT outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, two non-significant increases in TOT after the intervention were reported [ 33 , 93 ]. TOT was measured in various settings, including pediatric facilities [ 69 ], ambulance services [ 125 ], pharmacies [ 33 ], and operating rooms [ 93 , 126 ]. Table 5 depicts the findings of TOT outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Although TOT has been reported in previous studies as a frequent measure [12,129], we found only two studies reporting a reduction in three TOT outcomes. Both studies utilized lean and simulation in OR [152] or in a general hospital [143]. Similarly, two studies measured the percentage of LWBS with both reporting improvement after the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…This research project was chosen as part of a cyclic and interdisciplinary collaboration process in which team members worked by applying the DMAIC logic through the stages described in Deming's cycle (Plan-Do-Check-Act), which are foundational tools of lean thinking. In addition, we applied the Six Sigma methodology through the application of statistical analysis and monitoring of DPMO 21 .…”
Section: Methodsmentioning
confidence: 99%